The Use of Videos in Teaching - Some Experiences From the University of Copenhagen - Bregnhøj, Henrik; Neutzsky-Wulff, Chresteria; Ehrensvärd, Martin Gustaf; Rosthøj, Susanne; Sichlau Bruun, Camilla; Harker-Schuch, Inez Estelle; Lysák, Marin; Jae Chuang, Victoria (Tidsskriftet Læring og Medier (LOM), 2016)
This paper covers videos created and used in different learning patterns. The videos are grouped according to the teaching or learning activities in which they are used. One group of videos are used by the teacher for one-way communication, including: online lectures, experts interacting with one another, instruction videos and introduction videos. Further videos are teacher-student interactive videos, including: feedback on student deliveries, student productions and interactive videos. Examples from different courses at different faculties at The University of Copenhagen of different types of videos (screencasts, pencasts and different kinds of camera recordings, from quick-and-dirty videos made by teachers at their own computer to professionally produced studio recordings) as well as audio files are presented with links, as an empirical basis for the discussion. The paper is very practically oriented and looks at e.g. which course design and teaching situation is suitable for which type of video; at which point is an audio file preferable to a video file; and how to produce videos easily and without specialized equipment, if you don’t have access to (or time for) professional assistance. In the article, we also point out how a small amount of tips & tricks regarding planning, design and presentation technique can improve recordings made by teachers themselves. We argue that the way to work with audio and video is to start by analyzing the pedagogical needs, in this way adapting the type and use of audio and video to the pedagogical context.